Social Capital in Central Asia: How Does Civil Society Shape Democracy in The Region? - Ayushi Saini (Journal of Central Asian Studies)
Networks and mutual trust have long been integral to the traditions of Central Asian peoples. The collective cultural practices among nomadic populations have historically served as crucial tools for their survival. Social capital has influenced various aspects of Central Asian society since the Soviet era. Despite the Sovietization of local communities, traditional social actors continued to exist. Since gaining independence in 1991, institutions of social capital have played an important role in shaping the governance processes of Central Asian states. Social capital embodies the concept of "rule from below", which is a fundamental component of democratization. However, in Central Asia, while social capital institutions are pre-democratic, they still uphold democratic values. Informal communication, evident in various forms across the region, remains one of the primary sources of social capital. These forms can serve as carriers of democratic values. However, it is also essential to recognize the existence of negative social capital, which can adversely affect individuals or specific social strata. This paper aims to emphasize the role of traditional civil society, which constitutes social capital, in fostering democratic values in these countries. Additionally, it will highlight the significance of informal social and historical practices as elements of neo-institutionalism in Central Asia. This study will utilize a literature review methodology complemented by the author's analytical approach to address research gaps and provide evidence-based insights.